Pérdida del uso de la lengua kichwa en el entorno escolar, reflexiones para una educación intercultural en el Cantón Otavalo - Ipiales, Samia Y. (2023)
The loss of the Kichwa language in the Intercultural Bilingual Education Centers (CECIBS) in the Province of Imbabura is the problem to be analyzed in this essay. It is mentioned that one of the causes of the loss of the mother language, Kichwa, is the fact that it has not been taught and applied in the intercultural and bilingual schools of the canton since the school century since many teachers do not speak this language and practice it only in Spanish.